The Translator’s Ideology and the Reproduction of Superstructure - Bánhegyi, Mátyás (Working Papers in Language Pedagogy, 2009)
This pilot study investigates whether the translator's ideology affects the reproduction of superstructure in translated argumentative newspaper articles. The superstructure of a Hungarian argumentative newspaper article and its two English translations created by two translators with opposing ideologies are compared with the help of Hoey’s (2001) Superstructure Model. Based on the case study presented, it seems that the translator’s ideology does not affect the reproduction of superstructure in target texts.